The Potential and Development of Seaweed Cultivation in Lombok: A Review - Nunik Cokrowati; Yenny Risjani; Sri Andayani; Muhamad Firdaus (Jurnal Biologi Tropis, 2023)
The potential area of Lombok seaweed cultivation is 5490 Ha. The area utilized is 2039.63 Ha. The purpose of this paper is to review the diversity, cultivation activities, production and potential of seaweed to be developed, specifically focusing on aspects of cultivation and production on the island of Lombok, Indonesia. Macroalgae that have been cultivated on Lombok are Kappaphycus alvarezii morphotype brown and green and Gracilaria verucosa. The decline and the amount of uncertainty in production were caused by several problems in seaweed cultivation, weather changes, limited capital for production and decreased quality of seaweed seeds. The species that have the potential to be developed are Sargassum aquifolium, Caulerpa sp., Ulva sp., Eucheuma spinosum, and Gelidium sp. Development Locations are located throughout the waters in the shape of a bay and are by the stipulated water utilization spatial plan. Developing seaweed aqua tourism and institutional arrangements related to seaweed production is necessary.